Organic matter removal with bicarbonate-form ion exchange: water quality, kinetics and mass transfer mechanisms - Fernandez, Javier; Jarvis, Peter; Brookes, Adam; Knott, Stuart; Carra, Irene (Elsevier, 2021)
Ion Exchange (IEX) has been widely explored for the removal of organic matter. Chloride is traditionally used as counter-ion, but its release into water can increase the risk of corrosion. Research has shown that bicarbonate IEX can be an efficient alternative, and whilst some studies have compared its efficiency to chloride IEX, none have compared their performance in relation to the potential for disinfection by-product (DBPs) formation. The differences in organic matter removal between the two regenerants were assessed by looking at the molecular weight fractions derived from liquid chromatography organic carbon detection (LC-OCD) and dissolved organic carbon (DOC). Uptake kinetics, resin age and mass transfer diffusion were also investigated. DOC removal was similar for both chloride and bicarbonate resins, achieving ca 50% DOC removal. LC-OCD analysis revealed that organic matter between 0.35 and 1 kDa was the most efficiently removed, with slightly better uptake with bicarbonate IEX. However, these differences did not impact DBP formation potential. Trihalomethane (THM) and haloacetic acid (HAA) formation potentials followed the trends of DOC removal with up to 70% reduction after IEX treatment with both resin forms. However, the bromine substitution factor (BSF) increased with resin age -from 5 to 10% for THMs and from 4 to 7% for HAAs. Resin age resulted in up to 20% decrease in the organic matter uptake rates (from 0.19 to 0.15 min−1) and up to 34% decrease in pore diffusivities (from 9.4 × 10−12 to 7.1 × 10−12 m2/s for chloride IEX and from 1.0 × 10−11 to 6.6 × 10−11 m2/s).
Keywords: Disinfection by-products; HAAs; Mass transfer; Organic matter; THMs